Protein Post-translational Modifications in Head and Neck Cancer - Zhang, Hongbo; Han, Wei (Frontiers in Oncology, 2020)
Head and neck cancer (HNC) is one of the most common malignant tumors worldwide, and is prone to tumor recurrence and metastasis. At present, surgery combined with radiotherapy and chemotherapy is still the conventional treatment modality for patients with HNC. However, for patients with relapse or metastasis of HNC, the treatment outcome is not ideal, and the prognosis is poor. Thus, it is crucial to deepen the understand of tumor mechanisms. Post-translational modifications (PTMs) refer to covalent binding of small chemical molecular groups to amino-acid side-chain of proteins. PTM is an important regulator of protein function, and as such, a current research hotspot of epigenetics. In recent years, it has been found that tumor occurrence is often accompanied by the abnormality of PTMs. Indeed, the abnormality play an important role in tumor development, and can be used as a target for tumor diagnosis and treatment. To date, several types of protein PTMs involved in the development of HNC have been reported. This paper reviews the relationship between HNC and several major protein PTMs, including acetylation, methylation, and glycosylation, in order to provide clues for the future application about PTMs in diagnosis and treatment of HNC.